The Edukasi Perawatan Luka Dengan Metode Moist Wound Healing Pada Masyarakat Lumbung Mertah Kelurahan Martajaya - Ahmil Kiding; El Sinta Handayani; Ferawati Rusdianto; Hikmah Wati; Indar Ramadhanti; Juwilda; Mifta Nofita; Mita; Ni Wayan Widiadnyani; Riad Anugrah Putra Pratama (LPPM Universitas Widya Nusantara, 2025)
The community of Lumbug Mertah Hamlet, Martajaya Village, Pasangkayu Regency, is predominantly a farmer. Their agricultural activities are not without risks. The use of agricultural tools such as machetes, hoes, sickles, and other sharp agricultural tools often leads to problems such as wounds among farmers. Therefore, community education and practice are needed to address potential problems, including wound care education and practice. The method used was providing health education on modern wound care using the moist wound healing approach and practicing wound care using the moist wound healing approach. The results of the education and practice implemented in the community service program resulted in an increase in knowledge, with the percentage of people with good knowledge increasing from 15% to 92%, the percentage with sufficient knowledge decreasing from 77% to 8%, and the percentage with poor knowledge decreasing from 8% to 0%. Conclusion: The wound care education program using the moist wound healing approach improved the knowledge of the Lumbug Mertah Hamlet community regarding wound care.